Managing and Organizations : An Introduction to Theory and Practice - Clegg, Stewart R. (SAGE Publications, Ltd. (UK), 2024)
Covering the fundamentals of organizational behaviour, as well critically reflecting on the institutions and practices of business life, the seventh edition of Managing and Organizations has been updated to include:   A new chapter on Managing Diversity and Inclusion written by Martyna Sliwa, Professor of Business Ethics and Organisation Studies at Durham University Business School.   A new chapter on Managing Motivation—what drives individuals and teams to excel. • New and revamped case studies and examples from well-known organizations such as Nike, Tiffany, Nokia, Walmart and OpenAI.   An increased focus on sustainability and ethics, demonstrating how organizations can thrive whilst protecting people and planet.    This textbook is essential reading for anyone studying organizational behaviour at undergraduate or postgraduate level.  Stewart Clegg is Professor at the University of Sydney, Australia and Emeritus Professor at the University of Technology Sydney, Australia.  Tyrone S. Pitsis is Professor of Strategic Projects at the University of York, UK. Matt Mount is Associate Professor of Strategy at the University of Adelaide, Australia.